The Effectiveness of Back Adipose Vibration Therapy on Blood Pressure Homeostasis and Autonomic Nervous System Activation in Adolescents with Hypertension - Agus Setyo Utomo (Poltekkes Kemenkes Malang, 2021)
Adolescent hypertension is an increasing health issue that poses a risk of cardiovascular complications in adulthood. Back adipose vibration therapy is a non-pharmacological approach aimed at regulating blood pressure homeostasis by modulating the autonomic nervous system. This quasi-experimental study employed a pre-test and post-test design involving 30 hypertensive adolescents divided into an intervention group (n=15) and a control group (n=15). The intervention group received back adipose vibration therapy for four weeks, while the control group received no intervention. Blood pressure was measured before and after treatment using a digital sphygmomanometer, and autonomic nervous system activity was assessed through heart rate variability (HRV). The results showed that the intervention group experienced an average reduction in systolic blood pressure of 10 mmHg and diastolic blood pressure of 5 mmHg, whereas the control group only showed a decrease of 2 mmHg and 1 mmHg, respectively (p=0.02). Additionally, the intervention group exhibited a 15% increase in HRV, indicating enhanced parasympathetic activity and reduced sympathetic dominance. These findings suggest that back adipose vibration therapy is effective in lowering blood pressure and improving autonomic nervous system balance in hypertensive adolescents. Through mechanoreceptor stimulation and increased nitric oxide release, this therapy has the potential to serve as a non-pharmacological alternative for adolescent hypertension management in primary healthcare settings.